(untitled) (Journal of Architectural Design, 2024)
CO2 Hydrogenation to Aromatics Tandem Catalyst Methanol Synthesis in Oxides AreneBased Cyclization Over the past decades, great progress has been made in CO2 hydrogenation to a variety of C1 chemicals, lower olefins, and gasoline. However, due to the extreme inertness and high aromatization barrier of CO2, the synthesis of aromatics from one-shot CO2 hydrogenation is still a major challenge. Here, we present a tandem catalyst consisting of ZnO/ZrO2 and ZSM-5 zeolite for one-shot conversion of CO2 to aromatics with 70% selectivity, and the selectivity of incoming methane is suppressed to below 1%. The path of CO2 → CH3OH → aromatics over the tandem catalyst was demonstrated.